Restorative Justice–Based Tourism Investment Dispute Resolution Model: A Theoretical and Normative Study - Made Cinthya Puspita Shara; Putu Ade Harriestna Martana; Nyoman Satyayudha Dananjaya; Kadek Agus Sudiarawan (Journal Equity of Law and Governance, 2026)
This study aims to identify the challenges in resolving tourism investment disputes through a restorative justice approach, based on Howard Zehr's theory, and to assess the applicability of mediation mechanisms as an alternative form of inclusive and sustainable dispute resolution. Investment disputes in the tourism sector in Indonesia reflect the complexity of the relationship between economic, social, and cultural interests, especially when such investments impact the rights of local communities and environmental sustainability. This study employs a normative legal research method that combines a regulatory approach, a conceptual approach, and case studies. The study finds that Indonesia's formal legal system has not fully accommodated the need for the restoration of social relations in tourism investment conflicts. A restorative approach that emphasizes dialogue, participation, and restoration is important to integrate into dispute resolution policies. Mediation, as an ADR mechanism in line with the principles of restorative justice, has proven to be capable of providing more adaptive and participatory solutions. Therefore, it is necessary to strengthen regulations and institutions that support the application of restorative mediation within the national investment legal framework to promote fair, sustainable, and recovery-oriented tourism development.